China’s SHP Policy and its Role in Promoting SHP Development - Heng, Liu; Xiaobo, Hu; Shiji, Chu (Hydro Nepal: Journal of Water, Energy and Environment, 2018)
The development of China’s small hydropower (SHP) has a history of over 100 years. Especially after the formal establishment of the People’s Republic of China (PRC), China has attached great importance to the development of SHP and implemented specific policies to overcome the challenges at different stages of SHP development. This paper briefly introduces the management system of SHP in the Chinese context, reviews different policies related to SHP development, analyzes the role of different policies in promoting SHP development over time, and finally discusses the pertinence, effectiveness and sustainability of SHP policies. HYDRO Nepal JournalJournal of Water Energy and EnvironmentIssue No: 22Page: 25-33Uploaded date: January 14, 2018